موانع المسؤولية الجنائية -دراسة مقارنة بين الفقه الإسلامي والقانون الجزائري - - طهراوي, علي (University of eloued جامعة الوادي, 2016)
receiving this note highlights contraindications criminal responsibility through knowledge of the provisions relating to cases of lack of criminal responsibility in Islamic jurisprudence and Algerian law, and adopted for the study of this subject descriptive approach and analytical as well as comparative approach.Where he dealt with in the introductory chapter the concept of contraindications criminal responsibility in Islamic jurisprudence and Algerian law, through the definition of criminal responsibility and the statement of terms and replaced, and the definition of Mwanaha. In the first chapter I shared her personal inhibitions to lack of criminal responsibility, and exposed it to the inhibitions tics to lack of criminal responsibility and you through the definition of insanity, types and its impact on criminal liability, as well as the statement of a young age and carryover experienced by small and their impact on criminal responsibility, Also it addressed the inhibitions of volitional lack of criminal responsibility in which you define the sugar and release forms and its impact on In the second chapter of Foreign inhibitions to .criminal responsibility lack of criminal responsibility I dealt with through coercion definition and statement types and conditions and its impact on criminal liability, as well as the definition of necessity and impact statement terms of criminal responsibility.
شريعة وقانون
Keywords: موانع/المسؤولية الجنائية/القانون الجزائري; Contraindications/Criminal responsibility/Algerian law